Optimalisasi Literasi Digital oleh Pemerintah untuk Mendukung Agenda SDGs Goals-17: Partnership for The Goals - Novi Ramadani; Sintya Dwi Febrianti; Ichsan Fauzi Rachman (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Increasing digital literacy is the key to achieving the Sustainable Development Goals (SDGs), especially goal 17, namely partnerships to achieve the goals. It is hoped that government initiatives that provide facilities to increase partnerships and public awareness of digital literacy can increase the availability of information and provide equal opportunities for progress in the social, economic and environmental fields. This research uses literature review methods and content analysis. The results of this research state that the initiatives taken by the government to advance digital literacy have improved public service standards, especially in the fields of health, education and public services. The Indonesian government has fully supported the fulfillment of the Sustainable Development Goals (SDGs) by increasing public awareness and expertise in digital technology through various projects and programs. This program aims to increase community access and expertise in digital technology through training, creation of digital infrastructure, and public-private partnerships. This will significantly improve the quality of life of the community and participate in long-term development.